Plan de negocios para el servicio del cuidado al adulto mayor a adomicilio en la parroquia Cumbayá cantón Quito, provincia de Pichincha. - Cando Panchi, Vilma del Consuelo (2020)
The present project aims to develop a business plan in order to offer home care services to the elderly is aimed at meeting the needs of future customers, this service is intended for daily care, divided into day, night, hours, according to the need of the user will have trained staff for care. Within the market study, the information that can be obtained from the population of study is collected, which serves to analyze the supply, demand, unmet demand of the project and competition, to know the impact that could have the business in the market, the information is collected through the application of a survey, the same that allows to know the tastes and preferences of the elderly. In the technical study it helps to know the size and capacity of the project, for which, an investigation of the requirements that are needed for the correct operation of the service of the care to the elder, its macro and micro location, the characteristics of the place, size and capacity of the project, within this study is compiled all that it needs, the amount and monetary values, which serve to carry out the financial study. As the last study the Financial, this study helps to determine if the project is, feasible and profitable in the lapse of time, the purpose of this study is to analyze, to order the information that was obtained of the previous studies, to evaluate and thus to determine its yield, the project is made with the methodology of Plan of Business and the Model Canvas to explain the idea of the business